The Effect of Use Interactive Learning Media Environment-based and Learning Motivation on Science Learning Outcomes - Sahronih, Siti; Purwanto, Agung; Sumantri, M. Syarif (International Journal for Educational and Vocational Studies, 2020)
The study aims to determine the effect of the use of interactive learning media environment-based and learning motivation on science learning outcomes. This research was conducted on grade V students of SDN Wijaya Kusuma 07 Jakarta Barat from September to November 2019. The method used was an experiment with a research design using two-way ANAVA (treatment by level 2x2), with the sample of 61 students was obtained using a multi-stage random sampling. Based on data analysis, it was obtained: First, the science learning outcomes of students who learn to use interactive learning media environment-based are higher than the science learning outcomes of students who learn to use non-interactive learning media, as evidenced by Fcount (5.90) > Ftable (4.17 ); second, there was an effect of learning media interaction and learning motivation on the science learning outcomes, this can be seen from the acquisition price of Fcount (26.05) > Ftable (4.17); third, in groups of students who have high learning motivation, the science learning outcomes of students who learn to use interactive learning media environment-based are higher than the science learning outcomes of students who learn to use non-interactive learning media, with the Tukey-test Qcount Test (7.53) > Qtable (4.04); fourth, in groups of students who have low learning motivation, the science learning outcomes of students who learn to use interactive learning media environment-based are lower than the science learning outcomes of students who learn to use non-interactive learning media, with the Tukey-test Qcount Test (2.67) < Qtable (4.04).